Logistics Management at the Helvetia Health Center in Medan City - Alisa Ariani Sagala; Anna Kholijah; Mutiara Sofi; Yasmine Anta Syahrih; Ismi Larasati Hasibuan; Muhammad Rizky Ramadhan; Rapotan Hasibuan (Universitas Muhammadiyah Palu, 2025)
Logistics management in Community Health Centers plays an important role in ensuring the availability of medicines and medical devices that support health services to the community. This study aims to analyze the logistics management system in Helvetia Community Health Center, Medan City, with a focus on efficiency, stock availability, and distribution. The research method used is a descriptive approach with data collection through interviews, observations, and document analysis. The results of the study indicate that although there is a structured logistics management system, there are still challenges in terms of distribution delays and lack of real-time stock monitoring. To overcome this problem, it is necessary to implement a more modern logistics information system and increase human resource capacity. These findings are expected to provide strategic recommendations in improving the effectiveness of logistics management in Helvetia Community Health Center, so that it can support more optimal health services.